ELSiTO. A Collaborative European Initiative to Foster Social Inclusion with Persons Experiencing Mental Illness. (8th January 2013) - Ammeraal, M.; Kantartzis, S.; Burger, M.; Bogeas, T.; van der, C.; Vercruysse, L.
Abstract ELSiTO (Empowering Learning for Social Inclusion Through Occupation), an international collaborative partnership, with over 30 members from Belgium, Greece and the Netherlands, aimed to explore the nature and processes of social inclusion for persons experiencing mental illness. Members included persons experiencing mental illness and health professionals. Four international visits and local activities enabled a knowledge creation process that combined the experience of social inclusion as we lived and worked together with exploration of the processes of community projects, narratives of experiences and reflective workshops. Outcomes included identification and description of the following: the nature of social inclusion as lived by the participants; the critical elements that support inclusion; and the competences that are developed by all stakeholders during this process. The complex process of social inclusion is facilitated by doing together in environments that enable equality, trust, risk taking and realignment of power. These conceptual understandings of inclusion are discussed in relation to the ongoing activities of the partners, to their potential contribution to the education of occupational therapists (and other professionals) and to the development of socially inclusive occupation‐based projects in the community. Copyright © 2013 John Wiley & Sons, Ltd.